Alginate controls heartburn in patients with erosive and nonerosive reflux disease - Savarino, Edoardo (Baishideng Publishing Group Co., Limited, 2012)
AIM: To evaluate the effect of a novel alginate-based compound, Faringel, in modifying reflux characteristics and controlling symptoms. METHODS: In this prospective, open-label study, 40 patients reporting heartburn and regurgitation with proven reflux disease (i.e., positive impedance-pH test/evidence of erosive esophagitis at upper endoscopy) underwent 2 h impedance-pH testing after eating a refluxogenic meal. They were studied for 1 h under basal conditions and 1 h after taking 10 mL Faringel. In both sessions, measurements were obtained in right lateral and supine decubitus positions. Patients also completed a validated questionnaire consisting of a 2-item 5-point (0-4) Likert scale and a 10-cm visual analogue scale (VAS) in order to evaluate the efficacy of Faringel in symptom relief. Tolerability of the treatment was assessed using a 6-point Likert scale ranging from very good (1) to very poor (6). RESULTS: Faringel decreased significantly (P < 0.001), in both the right lateral and supine decubitus positions, esophageal acid exposure time [median 10 (25th-75th percentil 6-16) vs 5.8 (4-10) and 16 (11-19) vs 7.5 (5-11), respectively] and acid refluxes [5 (3-8) vs 1 (1-1) and 6 (4-8) vs 2 (1-2), respectively], but increased significantly (P < 0.01) the number of nonacid reflux events compared with baseline [2 (1-3) vs 3 (2-5) and 3 (2-4) vs 6 (3-8), respectively]. Percentage of proximal migration decreased in both decubitus positions (60% vs 32% and 64% vs 35%, respectively; P < 0.001). Faringel was significantly effective in controlling heartburn, based on both the Likert scale [3.1 (range 1-4) vs 0.9 (0-2); P < 0.001] and VAS score [7.1 (3-9.8) vs 2 (0.1-4.8); P < 0.001], but it had less success against regurgitation, based on both the Likert scale [2.6 (1-4) vs 2.2 (1-4); P = not significant (NS)] and VAS score [5.6 (2-9.6) vs 3.9 (1-8.8); P = NS]. Overall, the tolerability of Faringel was very good 5 (2-6), with only two patients reporting modest adverse events (i.e., nausea and bloating). CONCLUSION: Our findings demonstrate that Faringel is well-tolerated and effective in reducing heartburn by modifying esophageal acid exposure time, number of acid refluxes and their proximal migration.